2022
DOI: 10.1515/ijnes-2021-0138
|View full text |Cite
|
Sign up to set email alerts
|

The experience of novice nurse faculty in Saudi Arabia

Abstract: Objectives To understand the experience of novice nurse faculty members in Saudi Arabia and the influences on novice nurse graduates in their academic role. Methods A qualitative descriptive study grounded in naturalistic inquiry was used to better understand the experience of novice faculty in Saudi Arabia. Purposive sampling was used to recruit 10 novice nurse faculty from nursing schools in Saudi universities. Data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…The results from this research study align with the researcher’s previous study, focusing on the experience of new faculty members in the academic environment (Alanazi, 2022 ). Similarly, new faculty members felt lost without preparation for their roles, reflecting the results in this study where interns felt lost during their initial clinical experiences.…”
Section: Discussionsupporting
confidence: 86%
“…The results from this research study align with the researcher’s previous study, focusing on the experience of new faculty members in the academic environment (Alanazi, 2022 ). Similarly, new faculty members felt lost without preparation for their roles, reflecting the results in this study where interns felt lost during their initial clinical experiences.…”
Section: Discussionsupporting
confidence: 86%
“…For the final research question, participants reported that observing senior faculty was most helpful in preparing for their role; this finding is consistent with the theme “seeing glimmers of light” (Alanazi, 2022). Although most faculty participated in some professional development for the educator role, 7 percent of participants started in the faculty role without any preparation.…”
Section: Discussionsupporting
confidence: 70%
“…There have been limited published studies on Saudi nurse faculty competencies. Alanazi (2022) found that new faculty reported low levels of teaching competency because of workload and lack of preparedness. Mutair (2015) found that nurse faculty in SA demonstrated limited competencies in their ability to teach and motivate students to learn.…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabia, nurse education has developed from a one‐year program to a four‐year bachelor's degree (Alanazi, 2022; Almalki et al, 2011). The first nursing program was established in 1958, followed by a two‐year diploma program.…”
Section: Introductionmentioning
confidence: 99%